Bioactive compounds of hazelnuts as health promoters - Amaral, Joana S. (2016)
Hazelnut (Corylus avellana L.) belongs to the Betulaceae family and is one of the most popular and commonly consumed tree nuts worldwide. Hazelnuts are highly nutritious, providing macronutrients (fat, protein and carbohydrates), micronutrients (vitamins and minerals) and several bioactive phytochemicals. So far, different phytochemicals have been described in hazelnuts, such as phenolic acids, flavonoids, condensed tannins and phytosterols. Among the array of phytochemicals present in hazelnuts, several have been associated with interesting properties such as antioxidant, anti-inflammatory, anti-proliferative and hipocholesterolemic activities thus potentially contributing for beneficial health effects related to hazelnut consumption. Even though hazelnuts have a high fat content, its inclusion has been recommended as part of a healthy-diet. The health benefits of hazelnut consumption have been mainly associated with its favourable lipidic composition and fat-soluble bioactives but also to its content in other compounds such as L-arginine and antioxidant phytochemicals. This chapter aims at providing detailed and up-to-date information on hazelnut bioactive compounds composition and related health aspects, including data from epidemiological and clinical studies.